2010
DOI: 10.1111/j.1467-8624.2010.01479.x
|View full text |Cite
|
Sign up to set email alerts
|

What Paradox? Referential Cues Allow for Infant Use of Phonetic Detail in Word Learning

Abstract: Past research has uncovered a surprising paradox: although 14-month-olds have exquisite phonetic discrimination skills (e.g., distinguishing [b] from [d]), they have difficulty using phonetic detail when mapping novel words to objects in laboratory tasks (confusing "bin" and "din"). While some have attributed infants' difficulty to immature word learning abilities, the hypothesis presented herein is that infants are powerful word learners and this apparent difficulty occurs only when the referential status of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
249
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(263 citation statements)
references
References 30 publications
12
249
2
Order By: Relevance
“…First, this better represents everyday learning contexts, where words often do not occur in isolation (e.g., Aslin, Woodward, LaMendola, & Bever, 1996). Second, children might have had difficulty determining that a single, isolated novel word was a noun rather than an exclamation or command (e.g., Fennell & Waxman, 2010). Presenting the word in a sentence context avoided this interpretive difficulty.…”
Section: Methodsmentioning
confidence: 99%
“…First, this better represents everyday learning contexts, where words often do not occur in isolation (e.g., Aslin, Woodward, LaMendola, & Bever, 1996). Second, children might have had difficulty determining that a single, isolated novel word was a noun rather than an exclamation or command (e.g., Fennell & Waxman, 2010). Presenting the word in a sentence context avoided this interpretive difficulty.…”
Section: Methodsmentioning
confidence: 99%
“…Still, an alternative explanation for Rost and McMurray's (2009) findings of facilitative effects of talker variability on early word learning has also been proposed. Fennell and Waxman (2010) have suggested that hearing 18 talkers say both /buk/ and /puk/, consistently matched with the objects, might provide social evidence (rather than acoustic evidence) that /buk/ and /puk/ really are distinct (since 18 people think so). However, recent evidence indicates that even within-speaker acoustic variability can facilitate word learning if it is sufficiently large.…”
Section: What Can Acoustic Variability Tell Us About the Nature Of Inmentioning
confidence: 99%
“…Our results do not allow us to establish what exactly boosts subsequent semantic processing: familiarization of the voice, of the picture-word pairings, or a combination of the two. Previous research has shown that infants learn novel names for novel objects better when they first have the opportunity to see familiar objects paired with their basic level names (Fennell & Waxman, 2010;Namy & Waxman, 2000), presumably because this helps infants to better understand the purpose of the experiment (i.e. 'there will be pictures on the screen which will be named').…”
Section: Semantic Congruity Effectsmentioning
confidence: 99%